2022
DOI: 10.1007/s11606-022-07672-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Provider Perspectives on a Novel, Low-Threshold HIV PrEP Program for People Who Inject Drugs Experiencing Homelessness

Abstract: Background HIV outbreaks among people who inject drugs (PWID) and experience homelessness are increasing across the USA. Despite high levels of need, multilevel barriers to accessing antiretroviral pre-exposure prophylaxis (PrEP) for HIV prevention persist for this population. The Boston Health Care for the Homeless Program (BHCHP) initiated a low-threshold, outreach-based program to support engagement in PrEP services among PWID experiencing homelessness. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Four interviewers and a lead qualitative investigator developed a codebook collaboratively and iteratively [6]. We first independently read selected transcripts to develop potential codes and definitions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Four interviewers and a lead qualitative investigator developed a codebook collaboratively and iteratively [6]. We first independently read selected transcripts to develop potential codes and definitions.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing HIV transmission among PWID experiencing homelessness led BHCHP to develop a low-threshold program to increase PrEP access for their patient population [5]. Using data from qualitative interviews with a sample of BHCHP PrEP program participants [6], we conducted an initial exploration of the social experiences surrounding PrEP use among PWID experiencing homelessness. Although participants' median duration of PrEP use (six weeks) was relatively short, we found that, overall, most avoided disclosing their PrEP use widely in public or large group settings, but were much more willing to share their PrEP experiences with close social contacts such as friends and family members.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations